2019
DOI: 10.1177/0886260519867149
|View full text |Cite
|
Sign up to set email alerts
|

“When You’re in a Relationship, You Say No, but Your Partner Insists”: Sexual Dating Violence and Ambiguity Among Girls and Young Women

Abstract: Sexual dating violence (DV) is highly prevalent and associated with deleterious outcomes. Unfortunately, this form of violence remains poorly understood. Furthermore, the measures used to assess sexual DV may not account for the various manifestations of sexual DV, which limits our understanding of this problem. This study aimed to (a) explore how girls and young women describe their experiences of sexual DV and (b) explore whether the taxonomy on intimate partner sexual violence developed by Bagwell-Gray and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…Here, a youth's general inexperience of sexual relationships may also affect the perception of IPSV (Överlien, Hellevik, and Korkmaz 2019;Korkmaz forthcoming). Qualitative data have shown that girls express feeling like they owe sexual activities to their partner, and giving consent despite not really wanting to (Fernet et al 2019). Correspondingly, in one qualitative study, we showed that female youth might 'agree' to have sex as a way to protect themselves from further harm (Korkmaz and Överlien 2020).…”
Section: Unpacking Intimate Partner Sexual Violence -The Necessity Ofmentioning
confidence: 74%
See 3 more Smart Citations
“…Here, a youth's general inexperience of sexual relationships may also affect the perception of IPSV (Överlien, Hellevik, and Korkmaz 2019;Korkmaz forthcoming). Qualitative data have shown that girls express feeling like they owe sexual activities to their partner, and giving consent despite not really wanting to (Fernet et al 2019). Correspondingly, in one qualitative study, we showed that female youth might 'agree' to have sex as a way to protect themselves from further harm (Korkmaz and Överlien 2020).…”
Section: Unpacking Intimate Partner Sexual Violence -The Necessity Ofmentioning
confidence: 74%
“…Moreover, previous research shows that when sexual violence includes low invasiveness or force, participants tend to minimize or not recognize the behaviour as such (Fernet et al 2019). Here, a youth's general inexperience of sexual relationships may also affect the perception of IPSV (Överlien, Hellevik, and Korkmaz 2019;Korkmaz forthcoming).…”
Section: Unpacking Intimate Partner Sexual Violence -The Necessity Ofmentioning
confidence: 96%
See 2 more Smart Citations
“…The criterion of a minimum age differential between victim and perpetrator was applied, including in this range both the abuse of the adult and the minor towards the child. In addition, the presence of real or perceived coercion, with a negative reaction by the victim regarding physical contact and/or penetration, was also considered as abuse [ 41 ].…”
Section: Methodsmentioning
confidence: 99%